2002
DOI: 10.1046/j.1365-2605.2002.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐10 is highly expressed in the cryptorchid cryptepididymal epithelium: a probable mechanism preventing immune responses against autoantigenic spermatozoa in the epididymal tubule

Abstract: The expression of several immunoregulatory adhesion proteins and cytokines was studied in the normal epididymis, cryptorchid cryptepididymis, the epididymis of oestrogen‐treated mice and the epididymis of non‐obese diabetic (NOD) mice at the protein level to see which of these immunoregulatory proteins may be involved in lymphocyte regulation in the normal or pathological epididymis and if cytokine balance in this organ is on the cellular or humoral side. The aim of the study was to characterize the immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…These elevated cytokine levels may also have affected the induction of epididymitis in the VxCTGC group. Although it remains unknown which cell population produces each cytokine after Vx, it was reported that epithelial and myoid cells of the epididymis produce IL-10 and IL-6 respectively, in cryptorchid cryptepididymis (Verajankorva et al 2002). Clinically, the semen IL-6 level is increased in Vx reversal patients (Nandipati et al 2005).…”
Section: Effects Of Vasectomy On Testicular Autoimmunitymentioning
confidence: 99%
“…These elevated cytokine levels may also have affected the induction of epididymitis in the VxCTGC group. Although it remains unknown which cell population produces each cytokine after Vx, it was reported that epithelial and myoid cells of the epididymis produce IL-10 and IL-6 respectively, in cryptorchid cryptepididymis (Verajankorva et al 2002). Clinically, the semen IL-6 level is increased in Vx reversal patients (Nandipati et al 2005).…”
Section: Effects Of Vasectomy On Testicular Autoimmunitymentioning
confidence: 99%
“…The approach described in this article was based on the testable presumption that the epididymis, being an epithelial tube filled with immunologically foreign objects, must be balanced between tolerance and activation. There is strong biochemical evidence for such a dynamic balance in the epididymis (e.g., Jrad‐Lamine et al., ), and the presence of numerous cells of immune‐system origin within the epithelium is consistent with this view (Flickinger et al., ; Hermo and Robaire, ; Serre and Robaire, ; Verajankorva et al., ; Da Silva, ). This includes cells that stain for molecules found only in T lymphocytes, monocytes, dendritic cells, and macrophages.…”
Section: Discussionmentioning
confidence: 85%
“…The role that CD44 plays in ductal branching morphogenesis is not clear, but depends on interaction with hyaluronan [28]. Interestingly, both CD44 and hyaluronan have been found in mammalian adult epididymis and vas deferens [29, 30]. Furthermore, CD44 is required for limb outgrowth [31].…”
Section: Discussionmentioning
confidence: 99%